INTERACTION OF TRANSCRIPTION FACTORS PAX-5 AND STAT6 IN PATHOGENESIS OF ALLERGIC BRONCHIAL ASTHMA - V. N. Mineev; L. N. Sorokina; M. A. Nyoma; A. V. Eremeeva (Медицинская иммунология, 2014)
The aim of this work was to study an opportunity of coordinated expression of PAX-5 and STAT6 in bronchial asthma (BA) development. 35 healthy controls, 83 patients with allergic bronchial asthma (ABA) and 63 patients with nonallergic bronchial asthma (NABA) o different severity were observed. To evaluate PAX- 5 and β-actin mRNA levels, a reverse transcription-PCR with endpoint detection was applied. To determine STAT6 and pSTAT6 protein levels, ECL Western blotting protocols (Amersham) was used. A negative correlation was revealed between РАХ-5 and STAT6 mRNA expression levels in control group and in ABA. In NABA patients, the appropriate correlations were nonsignificant. Expression of РАХ-5 mRNA in ABA with normal IgE levels showed a significant negative correlation with that of STAT6. Meanwhile, expression levels of active pSTAT6 form in patients with high IgE and eosinophilia did negatively correlate with РАХ-5 mRNA expression. In ABA, effects of IL-4 caused a more significant decrease of РАХ-5 mRNA as compared with those in control group. The strongest negative correlation between РАХ-5 mRNA expression and STAT6 levels was revealed in groups with higher levels of mRNA РАХ-5 and lower levels of STAT6. The revealed negative correlations between STAT6 levels and РАХ-5 mRNA expression suggest that STAT6 may inhibit PAX-5 transcription in ABA group, thus, probably, promoting differentiation of B cells into plasma cells.